INCREASING THE ROLE OF POKDARWIS IN HUTUMURI COUNTRY, SOUTH LEITIMUR DISTRICT, AMBON CITY - Th Latupapua, Yosevita; Siahaya, Troice; Tjoa, Tine; Sahupala, Andjela; Silaya, Thomas; Boreel, Aryanto (LPPM Univ. Ibn Khaldun Bogor, 2023)
Community-based tourism development has become the best alternative in tourism management at the local level. Hutumuri Country is one of the customary countries in Ambon City that has the potential to develop community-based tourism. This PKM has the aim of increasing POKDARWIS's understanding of Objects and attractions, 4A, SAPTA PESONA, sustainable tourism, tourism villages, CHSE (Cleanliness, Healthy, Safety, Environment sustainability), and the realization of the role of POKDARWIS through Community-based tourism management in Hutumuri Country optimally and sustainably. The methods used are lecture and discussion methods, until PKM all pokdarwis members, and hutumuri state officials. The results of PKM showed a good and enthusiastic response from POKDARWIS in accepting PKM activities, the hasl was also seen from the pre-test results which only 10% understood and the post-test results showed a value of 100% understanding.